2016
DOI: 10.1016/j.biopsych.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Neural Reactivity to Emotional Stimuli Prospectively Predicts the Impact of a Natural Disaster on Psychiatric Symptoms in Children

Abstract: Background Natural disasters expose entire communities to stress and trauma, leading to increased risk for psychiatric symptoms. Yet, the majority of exposed individuals are resilient, highlighting the importance of identifying underlying factors that contribute to outcomes. Methods The current study was part of a larger prospective study of children in Long Island, NY (N = 260). At age 9, children viewed unpleasant and pleasant images while the late positive potential (LPP), an event-related potential (ERP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 70 publications
1
41
0
Order By: Relevance
“…Along similar lines, children high in temperamental fearfulness are at increased risk for developing anxiety symptoms (De Pauw and Mervielde, 2010), and an enhanced LPP to unpleasant images has been observed among offspring of parents with anxiety disorders (Nelson et al, 2015). In addition to internalizing symptoms, temperamental NA is a vulnerability for externalizing symptoms (Tackett et al, 2012), and we have previously shown that an enhanced unpleasant LPP prospectively predicted increases in externalizing symptoms in response to stress (Kujawa et al, 2016). …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Along similar lines, children high in temperamental fearfulness are at increased risk for developing anxiety symptoms (De Pauw and Mervielde, 2010), and an enhanced LPP to unpleasant images has been observed among offspring of parents with anxiety disorders (Nelson et al, 2015). In addition to internalizing symptoms, temperamental NA is a vulnerability for externalizing symptoms (Tackett et al, 2012), and we have previously shown that an enhanced unpleasant LPP prospectively predicted increases in externalizing symptoms in response to stress (Kujawa et al, 2016). …”
Section: Discussionmentioning
confidence: 74%
“…At the age 9 visit, participants completed an emotional interrupt task (Kujawa et al, 2016, 2013; Weinberg and Hajcak, 2011), which has previously been shown to reliably elicit an LPP in children and adolescents (Kujawa et al, 2013). The tasks includes presentation of pleasant, unpleasant, and neutral images from the International Affective Picture System (IAPS; Lang et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the series of positivities observed in the ERP wave likely reflect components of the P300 and LPP, which reflect attention towards and sustained processing of salient information and may be relevant to the development of both internalizing and externalizing symptoms in youth (Cuthbert, Schupp, Bradley, Birbaumer, & Lang, 2000; Foti et al, 2009; Kujawa et al, 2016; Kujawa, Hajcak, Torpey, Kim, & Klein, 2012; Kujawa, MacNamara, Fitzgerald, Monk, & Phan, 2015). Although our exploratory analyses did not reveal significant associations between depressive symptoms and the component consistent with LPP, we did observe an association with P300 to acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…9,36,37 The items were drawn from previous questionnaires developed for Hurricane Katrina 38 and Hurricane Ike. 39 The first 8 items were rated on a 5-point scale (1 = not at all affected, 5 = extremely affected), and included damage to home, safety threatened, financial hardship, children fear for their safety, life disrupted by the hurricane, difficulty finding gasoline, difficulty getting food, water, or warmth, and children quarreling or complaining more than usual.…”
Section: Methodsmentioning
confidence: 99%